Effects of pilates method in low back pain - Rodrigues, Thalita dos Santos; Oliveira, Jefferson Quaresma de; Matos, Ludmilla Karen Brandão Lima (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Back pain is all pain conditions, located in the lower back, between the last rib and the gluteal fold. The main goal of Pilates is to strengthen the center of the body, improving spinal stabilization. Objective: This study aimed to examining the effects of Pilates on low back pain, checking their effect on low back pain, using a visual analog pain scale, assess the quality of life through the Quality of Life Questionnaire - WHOQOL Bref and measure flexibility by Test FINGER-FLOOR. Method: This study was submitted to the ethics committee of a private college in Teresina, PI (no. 18441813.0.0000.5211). The sample was not random type, consisting of six participants with low back pain. They were assessed before and after treatment by means of an evaluation form (age, weight, height, BMI, visual analog pain scale - EVA Test and finger-floor) and the Quality of Life Questionnaire - WHOQOL Bref. 10 individual sessions were conducted with the Pilates method, often two weekly visits lasting one hour each. Data were analyzed using parametric test “t” test, with significance level of p ≤ 0.05. Results: The results showed that treatment significantly reduced pain, with p = 0. 0048. Regarding quality of life, we can observe significant improvements in the Physical Domain with p = 0.0288, and p = Psychological Domain. 0.0477. Already in Social Domains, Domain Environment and overall quality of life, the results were not significant with p = 0.2894, p = 0.6357 and p = 0.0830, respectively. Flexibility in the analysis of observed significant improvement, with p = 0.0039. Conclusion: Therefore, the Pilates Method can be an effective treatment option in the treatment of lumbago, acting globally.